Factors influencing public participation behavior relating to government microblogs on COVID-19 updates - Shao, Peng; Li, Menglei (Frontiers in Public Health, 2024)
During the global COVID-19 pandemic, densely populated megacities engaged in active international exchanges have faced the most severe impacts from both the disease and the associated infodemic. This study examines the factors influencing public participation behavior on government microblogs in these megacities during the pandemic. It guides megacities in disseminating epidemic information, promoting knowledge on epidemic prevention, managing public opinion, and addressing related matters. Utilizing the elaboration likelihood model’s central and peripheral routes, this study analyses the influence mechanisms influencing public participation behavior and reveals the regulatory role of confirmed case numbers. Drawing on an empirical analysis of 6,677 epidemic-related microblogs from seven Chinese megacities, the study reveals that microblog content richness demonstrates a U-shaped impact on public participation behavior. Conversely, content interaction, content length, and the number of fans positively impact participation, while update frequency has a negative impact. Additionally, the number of new confirmed cases positively regulates the impact of microblog content and publisher characteristics on public participation behavior. Public participation behavior also varies based on publishing time and content semantic features. Finally, a qualitative comparative analysis examines and discusses different configurations of influential factors.